Human Resource Accounting and Shareholders Wealth Maximization: Empirical Study of Nigeria Quoted Manufacturing Firms - Stanley Diepiriye, Davies (International Journal of Business and Management Future, 2018)
This study empirically investigated the relationship between human resource accounting and shareholders wealth maximization of selected quoted manufacturing firms in Nigeria from 2000-2016. Time series data was generated from the Annual Reports of the quoted firms. Twenty manufacturing firms were selected from the population of quoted manufacturing firms. Two multiple regression models were specified and estimated with the aid of Software package for social services (SPSS). Return on investment was modeled as the function of capital and revenue expenditure components of human resource accounting. The generated collinearity diagnostics result shows that the Eigen values that correspond to the highest condition index and variable constant are consistent with the rule of thumb. The Durbin Watson test shows absence of auto-correlation. From the expenditure component, we found correlation coefficient of 71.3%, R2 and the Adjusted R2 shows that 50.8% and 36.0%. The explanatory power of the predictor variables shows that all the independent variables have positive but insignificant relationship with return on investment of the manufacturing firms except cost of human resource acquisition. The revenue expenditure proved R2 and the adjusted R2 of 61.0% and 49.3% explained variation on return on investment. The coefficient of the independent variables proved that salaries, wages and bonus have positive relationship with return on investment of the selected manufacturing firms while commission and allowances have positive effect on return on investment. It concludes that human resource accounting has significant relationship with shareholders wealth maximization of the selected manufacturing firms. We recommend that all human capital expenditure should properly be accounted for and the need to investment on human capital of the firms.